Condylostylus Bigot from Vietnam with description of a new species and a key to Vietnamese species (Diptera: Dolichopodidae) - Li, Xuankun; Li, Zhu; Yang, Ding (Zootaxa, 2012)
Previously only one species of the genus Condylostylus Bigot was known to occur in Vietnam. Here six species of Condylostylus are recorded from Vietnam, including Condylostylus vietnamensis sp. nov. A key to the species of the genus from Vietnam is provided.